2021
DOI: 10.1038/s41598-021-03804-9
|View full text |Cite
|
Sign up to set email alerts
|

Etazene induces developmental toxicity in vivo Danio rerio and in silico studies of new synthetic opioid derivative

Abstract: Synthetic opioids are gaining more and more popularity among recreational users as well as regular abusers. One of such novel psychoactive substance, is etazene, which is the most popular opioid drug in the darknet market nowadays. Due to limited information available concerning its activity, we aimed to characterize its developmental toxicity, including cardiotoxicity with the use of in vivo Danio rerio and in silico tools. Moreover, we aimed, for the first time, to characterize the metabolite of etazene, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…In a recent report on N-piperidinyl etonitazene, it was already suggested that some metabolites would undergo glucuronide conjugation, but no actual conjugates were found. 14 The present findings are comparable with results obtained in a recent etazene metabolism study performed in zebrafish 6 and rats. 21 As metabolism of drugs may differ for zebrafish/rats and humans due to species differences in, for example, expression of metabolic enzymes, it is important to confirm this in human samples.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In a recent report on N-piperidinyl etonitazene, it was already suggested that some metabolites would undergo glucuronide conjugation, but no actual conjugates were found. 14 The present findings are comparable with results obtained in a recent etazene metabolism study performed in zebrafish 6 and rats. 21 As metabolism of drugs may differ for zebrafish/rats and humans due to species differences in, for example, expression of metabolic enzymes, it is important to confirm this in human samples.…”
Section: Resultssupporting
confidence: 91%
“…However, two less abundant N-oxide metabolites were not detected in the human urine and conversely no phase II metabolites were found in the rat samples. 21 In the zebrafish, only the N-dealkylated metabolite M2 was detected, 6 which in the human urine sample was only present in a small amount. Next to the species difference, time between drug intake and sampling and differences in used analytical techniques should also be considered to explain these (small) discrepancies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations